Determination of Adrenosterone and its Metabolites in Human Urine by LC/APCI/MS and GC/MS - Han, Eunjung; Yim, Okkyoung; Beak, Sun-young; Chung, Jaeyeon; Lee, Ji-hye; Kim, Jungahn; Kim, Yunje (WILEY-V C H VERLAG GMBH, 2009)
This study was done for the determination and excretion profile of adrenosterone and its metabolites in human urine using both liquid chromatography with atmospheric pressure chemical ionization mass spectrometry and gas chromatography with mass spectrometry. Adrenosterone and its two metabolites were detected in human urine after administration a healthy volunteer with 75 mg of adrenosterone. We found that adrenosterone-M I (C19H26O3) was a reduction and adrenosterone-M2 (C19H26O4) was a hydroxylation at C-ring, which did not know the exact position of the C-ring. The adrenosterone parent was detected by GC/TOF-MS, but not detected by LC/APCI/MS because of low intensity. Adrenosterone and its two metabolites were excreted as their glucuronided fractions. The recovery of this method ranged from 100.7 to 118.4% and the reproducibility and accuracy test were 85.5 to 112.0% and 1.1 to 8.4%, respectively. The excretion studies showed that adrenosterone and its metabolites were detectable in human urine during a 48 h period after oral administration, with maximum level of excretion at 4.1 h. The glucuro-/sulfa-conjugated ratio of adrenosterone, M1 and M2 was 0.73 +/- 0.03, 0.96 +/- 0.06 and 0.89 +/- 0.03 (n = 6), respectively. The amounts of adrenosterone excreted in urine were 14.75 ng for 48 h. Also, the maximum level of androsterone and 11 beta-hydroxy androsterone, which were endogenous steroids, were reached 4.1 h after the oral administration of adrenosterone.
Keywords: CHROMATOGRAPHY-MASS-SPECTROMETRY; ANABOLIC-STEROIDS; GLUCURONIDE; IONIZATION